Step-induced defects in thin films and the effect on their electrical and magnetic properties - Syrlybekov, Askar (Trinity College (Dublin, Ireland). School of Physics, 2015)
This thesis investigates step-induced defects in thin films and their effect on the electrical and magnetic properties. Stepped epitaxial Fe3O4 thin films with different thickness were fabricated and their magnetic properties were investigated. The magnetization measurements suggest that the steps induce an additional anisotropy, which has an easy axis perpendicular to steps and the hard axis along the steps. In addition, electrical analysis of a Fe3O4 film grown on stepped SrTiO3 substrate revealed anisotropic resistive switching. When the current was directed parallel to the step-edge direction, lower voltages were required to switch to the lower conducting state than the case where current was perpendicular to the step-edges. This is attributed to the high density of antiphase boundaries present at step edges. In order to control defect densities, a thorough study was carried out to control periodicity and height of the vicinal MgO (100) substrates which is instigated by annealing them at high temperature in air. Furthermore, transport measurements on trilayer graphene synthesized on vicinal cubic-SiC(001), clearly demonstrate that the self-aligned periodic nanodomain boundaries (NBs) induce a charge transport gap.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.